Peripheral Fluorescein Angiographic Findings in Fellow Eyes of Patients with Branch Retinal Vein Occlusion - Irena Tsui; Asima Bajwa; Valentina Franco-Cardenas; Carolyn K. Pan; Hanna Y. Kim; Steven D. Schwartz (International Journal of Inflammation)
Introduction. Branch retinal vein occlusion (BRVO) is a common retinal vascular condition that results in intraocular inflammatory changes. Ultra wide field fluorescein angiography (UWFFA) is a retinal imaging device that can capture peripheral retinal findings. The purpose of this study was to look for peripheral findings in the fellow eye of patients with BRVO using UWFFA. Methods. Retrospective imaging review of patients diagnosed with BRVO that had both eyes imaged with UWFFA. Images were graded for peripheral findings in other quadrants of the same eye as well as in all quadrants of the fellow eye. Results. Of 81 patients, 14 (17%) patients had late vascular leakage in a quadrant other than the BRVO distribution. Five (6%) findings were in the same eye, 8 (10%) findings were in the fellow eye, and 1 (1%) finding was in both the same eye and the fellow eye. Of these 14 patients, 11 (80%) patients had hypertension. Conclusion. Late peripheral retinal leakage in the fellow eye of patients with BRVO was detected in this cohort of patients with UWFFA. This novel finding may represent underlying systemic inflammation, hypertension, or bilateral BRVOs.